2004
DOI: 10.1007/s00381-003-0840-z
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the pathways responsible for cerebrospinal fluid absorption in the neonate

Abstract: The data suggests that neonatal CSF can be absorbed directly into the cranial venous system. However, contrary to the classical view, this route may represent an auxiliary system that is recruited to compliment lymphatic transport when intracranial pressures are very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 29 publications
1
53
0
2
Order By: Relevance
“…Tracers injected directly into the CSF of rodents drain through channels in the cribriform plate into lymphatics of the nasal mucosa and from there to cervical lymph nodes (Cserr and Knopf, 1992;Kida et al, 1993;Knopf et al, 1995;Carare et al, 2008). In humans, CSF also drains through the cribriform plate to nasal lymphatics (Papaiconomou et al, 2004;Zakharov et al, 2004a). The bulk of the CSF, however, drains directly back into the blood through arachnoid granulations and villi, in the walls of intracranial and spinal venous sinuses (Weed, 1923;Weller, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Tracers injected directly into the CSF of rodents drain through channels in the cribriform plate into lymphatics of the nasal mucosa and from there to cervical lymph nodes (Cserr and Knopf, 1992;Kida et al, 1993;Knopf et al, 1995;Carare et al, 2008). In humans, CSF also drains through the cribriform plate to nasal lymphatics (Papaiconomou et al, 2004;Zakharov et al, 2004a). The bulk of the CSF, however, drains directly back into the blood through arachnoid granulations and villi, in the walls of intracranial and spinal venous sinuses (Weed, 1923;Weller, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…The initial spike in blood tracer concentrations may have been due to direct transport of HSA into the cranial veins, as the intracranial pressure would be expected to increase temporarily due to the tracer injection into the ventricle. In past studies, we observed some transient direct CSF-cranial venous transport when intracranial pressure was elevated abruptly to high levels (36,46). However, the 10-min delay in the peak concentration of tracer in blood (40 min) compared with the turbinates (30 min) seems consistent with the view that a significant amount of the tracer made its way into blood after first traversing the lymphatic network in the olfactory turbinates, moving through the cervical lymphatics, and finally transporting into the venous system at the base of the neck.…”
Section: Discussionmentioning
confidence: 97%
“…tracer into the cranial venous system in sheep and observed that tracer entry into the superior sagittal sinus only occurred at high intracranial pressures (36,46). One possibility is that the arachnoid projections divert CSF from the cranium when intracranial pressure is transiently or chronically elevated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas originally it was assumed that the majority of CSF convected through the arachnoid villi and granulations into the cranial venous sinuses, the quantitative data suggests that the importance of this transport may have been exaggerated [12, 13]. Mounting evidence suggests that CSF drainage into extracranial lymphatic vessels cannot be ignored as studies in animal models indicate that a significant portion if not the majority of CSF transport can occur via this route [5, 6].…”
Section: Discussionmentioning
confidence: 99%